Pengaruh Kurs Valuta Asing terhadap Nilai Ekspor Teh Kayu Aro pada PT. Perkebunan Nusantara VI - Johandri Iqbal; Heriyani Heriyani; Anggun Wigiarti (Global Financial Accounting Journal, 2022)
Purpose - The purpose of this research activity is to assess how much influence the foreign exchange rate has on the export value of orthodox wood aro tea exported by PT. Perkebunan nusantara VI. Research Method - This study uses secondary data with the type of time series data or the so-called time series, the analytical method used is descriptive analysis which is arranged in tabular foem. Meanwhile, to assess the effect of the foreign exchange rate on the export value of tea kayu aro, the researchers used the Ordinary Least Square (OLS) model of regression analysis. Findings - This result is fully supported by the theory of depreciation and appreciation of the exchange rate, both of which affect consumer demand and purchasing power. When the exchange rate depreciates, the selling price of export products will decrease in the international market. However, when there is an appreciation of the exchange rate, the selling price of export products will increase due to the high exchange rate Implication - From the resukts of the study, it was stated that the foreign exchange rate had an effect on the export of tea kayu aro, but the effect was not too large. Therefore, it is hoped that later PT. Perkebunan Nusantara VI can pay more attention to the linkages and continuity of the export process of tea kayu aro, so that later the export value of tea kayu aro can always be at a stable amount.